Efficiency Of Transition From Manual Medical Records To Electronic Medical Records On The Speed Of Patient Service At RSU Royal Prima Medan - Laurenxius, Vanessa Sinana; Ginting, Chrismis Novalinda; Ginting, Rapael (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
In the digital era, the integration of quality and routine data is key to transforming healthcare services. The utilization of information technology continues to grow, spanning from planning to providing individual and community health data. One of the innovations implemented is the transition from manual medical records to electronic medical records (RME), which despite its many benefits, still faces various challenges. RSU Royal Prima Medan started this transition process at the end of 2023 until early 2024, with the main obstacles being infrastructure limitations, suboptimal system integration, and adaptation difficulties that impacted the efficiency of patient services. This study aims to analyze the efficiency of the RME transition in improving patient service speed at RSU Royal Prima Medan. The method used was descriptive qualitative with an exploratory approach, involving in-depth interviews, direct observation, and document analysis. Data were analyzed using the Miles and Huberman interactive model. The results showed that the implementation of RME has achieved about 80% effectiveness in improving service efficiency. The data retrieval process became 50% faster than the manual system, while the RME utilization rate reached 85%. Patient waiting time was also reduced by an average of 15 minutes per consultation. Despite this, obstacles such as network instability and technical issues were still encountered. In conclusion, the transition to RME at RSU Royal Prima Medan has improved service efficiency and patient data management. However, continuous system development, more comprehensive integration, as well as infrastructure improvements are needed to optimize the benefits of RME in improving healthcare quality